Effect of Sampling Temperature on the Properties of Inorganic Particulate Matter Collected from Biomass Combustion in a Drop-Tube Furnace - Gao, Xiangpeng; Wu, Hongwei (American Chemical Society, 2010)
Sampling temperature is found to significantly influence the properties of PM10 (particulate matter with an aerodynamic diameter less than 10.0 μm) collected from the combustion of pulverized biomass (75−150 μm) in a laboratory-scale drop-tube furnace system at 1300 °C. Although the PM1.0 yield remains constant, the mass of PM1.0 shifts to a larger size at a lower sampling temperature, apparently due to particulate coagulation. PM1.0 dominantly contains Na, K, and Cl, and the mass size distribution of these elements also shifts to a larger size as the sampling temperature decreases. However, PM1.0−10 dominantly consists of Ca, Mg, and S. Increasing sampling temperature reduces PM loss due to gravitational settling deposition, leading to an increase in the PM1.0−10 yield. The mass of Mg and Ca in PM1.0−10 also increases with increasing sampling temperature and reaches constant values at sampling temperatures close to the flue gas temperature (115 °C). The sampling temperatures at which drastic shifts in particle size distribution and elemental mass size distribution of PM10 take place correlate well with the SO3 dew points of the flue gas. The results in this study suggest that the sampling temperature of PM should be above the flue gas acid dew point to prevent the condensation of acid gas and, furthermore, be kept close to or same as the flue gas temperature in order to suppress particulate coagulation and gravitational settling deposition.